Harmonizing Contemporary International Commercial Law with Sharia-Based National Legal Systems: A Comparative Study of Pakistan, Turkey, Indonesia, Malaysia, and Saudi Arabia - Muhammad Azam; Anis Mashdurohatun; Angga Nugraha Firmansyah; Muhammad Dias Saktiawan; King On Putra Jaya (MILRev: Metro Islamic Law Review, 2025)
This study examines the harmonization of International Commercial Law (ICL) with Sharia-based national legal systems in five member states of the Organization of Islamic Cooperation (OIC): Pakistan, Turkey, Indonesia, Malaysia, and Saudi Arabia. These countries were deliberately selected for their diverse legal traditions, varying levels of economic development, and differing degrees of Sharia implementation within their domestic legal orders. Using a qualitative-comparative approach, the research draws on academic literature, national legal documents, and relevant international legal instruments to analyze the interaction between global commercial norms and Islamic legal principles. The analysis identifies thematic trends, methodological approaches, and significant findings from previous scholarship on the intersection of ICL and Sharia. The findings reveal divergent trajectories: Malaysia and Turkey have successfully integrated ICL provisions into their domestic frameworks through institutional reforms and adaptive jurisprudence. In contrast, Pakistan and Saudi Arabia face persistent conceptual and normative challenges, particularly in reconciling modern commercial practices with strict interpretations of Sharia. Indonesia represents a hybrid model, blending secular legal norms with religious values to produce a contextually balanced system. By mapping these comparative experiences, this study contributes to the discourse on legal pluralism and provides insights for policymakers and scholars seeking to develop context-sensitive models for integrating transnational commercial law into modern Islamic legal systems.